Simulation of effect of various distances between front and rear body on drag of a non-circular cylinder - Sajali, Muhammad Fahmi Mohd; Syed, Ashfaq; Aabid, Abdul; Khan, Sher Afghan (academia Baru, 2019)
Numerical investigation of a non-circular cylinder (D-shaped bluff body) of fore body, geometrical effects on the drag as well as on the flow-field were simulated at the subcritical flow regime at a velocity of 26.84 m/s. The non-circular cylinder (D-shaped model) front surface for a positive pressure of the unsteady vortex generation in the near wake, the square plate was attached upstream of the non-circular cylinder as the base model. The forebody modifies the streamlines that separate from its edges to attach smoothly onto the front face shoulders of the main body, thereby converting the bluff body into an equivalent streamlined body, resulting in minimum drag. The height of the forebody (B1) is 25 mm, and the length of the front body (L2), was in the range from 0.25B2 to 1.75B2. The results obtained from the simulation are compared with the experimental results. The results indicate that the side faces and the rear faces are subjected to low pressure, whereas the front face is experiencing high positive pressure. With this flow pattern, the pressure drag coefficient assumes a substantially significant value in the range of 1.0 - 1.42. Such a high value of drag coefficient is particularly valid for bluff bodies with noncircular cross-sections with the sharp corners.